Some Fixed Point Results in Fuzzy Metric Space - Manandhar, K.B.; Jha, K. (Kathmandu University Journal of Science, Engineering and Technology, 2015)
The purpose of our paper is to study the fixed point theorems in different types of fuzzy metric space using different types of contractive conditions.